2022
DOI: 10.1002/jmv.27729
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single‐dose antiviral drugs for influenza treatment: A systematic review and network meta‐analysis

Abstract: To conduct network meta-analysis (NMA) of clinical efficacy and safety of singledose antiviral drugs, grouped by dosage, in treatment of influenza. Systematic retrievals were conducted in databases, including Pubmed, Embase, Web of Science, the Cochrane Register of Clinical Trials and from the website ClinicalTrials.gov, for clinical trials recorded between the interception of the databases and March 31, 2021. Randomized controlled trials (RCTs) of influenza treatment in which singledose antiviral drugs were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Several network meta-analyses have evaluated antivirals for treating influenza [8][9][10]42,43 , but none assessed all approved antivirals for influenza and none focused on patient-important outcomes of mortality and admission to hospital. Compared with previous network meta-analyses [8][9][10]42,43 , we included more trials and patients, assessed the certainty of evidence using the GRADE approach, and presented absolute effects. Our findings on baloxavir are consistent with previous network meta-analyses that baloxavir probably reduces time to alleviation of symptoms without increasing adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several network meta-analyses have evaluated antivirals for treating influenza [8][9][10]42,43 , but none assessed all approved antivirals for influenza and none focused on patient-important outcomes of mortality and admission to hospital. Compared with previous network meta-analyses [8][9][10]42,43 , we included more trials and patients, assessed the certainty of evidence using the GRADE approach, and presented absolute effects. Our findings on baloxavir are consistent with previous network meta-analyses that baloxavir probably reduces time to alleviation of symptoms without increasing adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews and network meta-analyses have assessed the effects of antiviral drugs for treating influenza [8][9][10] , but have been limited in failure to provide absolute effects of interventions, [8][9][10] in their focus solely on specific categories of interventions such as neuraminidase inhibitors or particular subtypes of influenza such as seasonal influenza, [8][9][10] or overlooked crucial patient-important outcomes including mortality and hospitalization. [8][9][10] Additionally, some studies 9,10 do not assess the certainty of the evidence and none include recent trials.…”
Section: Introductionmentioning
confidence: 99%
“…A network metanalysis of 12 RCTs has shown that peramivir is superior to baloxavir and laninamivir in time to alleviation of symptoms, whereas baloxavir has the best efficacy in antipyretic time, virus titre variations against the baseline 24 and 48 h after medication and adverse events. 109 Albeit each individual drug leads to marginal benefit, combinations of directly acting antivirals as well as combination of antivirals with host-directed therapies (nitazoxanide, 110,111 COX-2 inhibitors, mTOR inhibitors, antioxidants) could deliver better efficacy and less resistance development.…”
Section: Substrate Inhibitors Of Polymerasementioning
confidence: 99%
“…In contrast, baloxavir was associated with a reduced rate of influenza-related complications [70]. Another network meta-analysis comparing single-dose anti-influenza treatments (peramivir, laninamivir, and baloxavir) found that peramivir is superior to baloxavir and laninamivir in TTAS, whereas baloxavir has the best efficacy in antipyretic time, virus titer variations against the baseline 24 and 48 h after medication and adverse events [71].…”
Section: Endonuclease Inhibitormentioning
confidence: 99%